A REVIEW ON HERBAL THERAPY FOR RESPIRATORY AILMENTS: Pharmaceutical Science-Biotechnology - RACHANA; MAMTA PANT; SUJATA BASU; AYUSHI JAIN; NITIN GOEL; ISHAN WADI (International Journal of Life Science and Pharma Research, 2022)
Human beings are dealing with various types of stresses in the modern day’s life style and this includes the habit of tobacco smoking also. These stressors cause an imbalance between the antioxidant-oxidant species in the body and leads towards inflammatory conditions. There are various herbs which are already included in Indian diet to deal with such situation and examples are the daily flavours like: turmeric, ginger, and cumin and many more. The present study is an investigation to analyze the antioxidant nature of a specific herb Adhatoda vasica, majorly used for respiratory ailments, to neutralize tobacco smoke induced oxidative stress. The results depict that, Adhatoda vasica has a beneficial effect on the antioxidant system of the cells and prevents the toxicity caused by tobacco smoke which results in reduction in cell death.